SMART APPS CREATOR-BASED INTERACTIVE LEARNING MEDIA: ENHANCING CRITICAL THINKING SKILLS - Istiqomah, Siti; Murwaningsih, Tri; Sukarno, Sukarno (Universitas Labuhanbatu, 2025)
Purpose – This study aimed to develop and assess the effectiveness of Smart Apps Creator (SAC)-based interactive learning media to enhance critical thinking skills among fifth-grade students in Natural and Social Sciences (IPAS) learning.Methodology – Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study employed a quasi-experimental design with purposive sampling for the needs analysis (20 teachers, 24 students) and random sampling for the trials (54 experimental and 57 control group students across four elementary schools). The experimental group engaged in six offline SAC-based learning sessions, while the control group used conventional methods (lectures, worksheets, static images). Data were collected through classroom observations, media feasibility questionnaires, and pre- and post-tests of critical thinking skills, and analyzed using descriptive statistics, paired t-tests, and N-Gain scores.Findings – The SAC-based media achieved high feasibility (expert validation: 82.3%-86.5%). They significantly improved critical thinking, with the experimental group recording an N-Gain of 0.75 (high) and a t-value of -30.556 (p = 0.000), outperforming the control group’s N-Gain of 0.42 (moderate) and a t-value of -18.070 (p = 0.000). Interactive elements, such as quizzes and animations, fostered student-centered learning, although challenges included limited hardware and teacher training needs. The offline SAC media effectively addressed connectivity constraints, enhancing analytical skills.Contribution – This study offers a scalable, offline educational technology solution for rural areas, promoting 21st-century skills such as critical thinking and suggesting the broader implementation and exploration of additional skills, including collaboration and communication.